1994
DOI: 10.1086/174817
|View full text |Cite
|
Sign up to set email alerts
|

Inside the supernova: A powerful convective engine

Abstract: We present an extensive study of the inception of supernova explosions by following the evolution of the cores of two massive stars (15 M ⊙ and 25 M ⊙ ) in multidimension. Our calculations begin at the onset of core collapse and stop several hundred milliseconds after the bounce, at which time successful explosions of the appropriate magnitude have been obtained. Similar to the classical delayed explosion mechanism of Wilson (1985), the explosion is powered by the heating of the envelope due to neutrinos emitt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
704
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 628 publications
(722 citation statements)
references
References 0 publications
16
704
1
1
Order By: Relevance
“…Second, material advecting toward the gain surface is continually heated by neutrinos, gaining entropy as it moves inwards. As has been pointed out by many authors (e.g., Herant et al 1992Herant et al , 1994Janka & Müller 1993;Burrows et al 1995;Janka & Müller 1995;Thompson 2000;Janka 2001;Fryer & Warren 2004;Thompson et al 2005;Bruenn et al 2006;Buras et al 2006b;Murphy & Burrows 2008;Scheck et al 2008;Müller et al 2012a), convective flows enhance the conditions necessary for the revival of the shock. They increase the effective neutrino heating efficiency because rising fluid elements have lower neutrino emissivities after adiabatic expansion, reducing losses due to neutrino cooling, and the non-radial motions increase the dwell time of fluid elements in the gain region, thereby increasing the time they are subject to neutrino heating.…”
Section: Development Of Instabilities and Asphericitymentioning
confidence: 82%
See 2 more Smart Citations
“…Second, material advecting toward the gain surface is continually heated by neutrinos, gaining entropy as it moves inwards. As has been pointed out by many authors (e.g., Herant et al 1992Herant et al , 1994Janka & Müller 1993;Burrows et al 1995;Janka & Müller 1995;Thompson 2000;Janka 2001;Fryer & Warren 2004;Thompson et al 2005;Bruenn et al 2006;Buras et al 2006b;Murphy & Burrows 2008;Scheck et al 2008;Müller et al 2012a), convective flows enhance the conditions necessary for the revival of the shock. They increase the effective neutrino heating efficiency because rising fluid elements have lower neutrino emissivities after adiabatic expansion, reducing losses due to neutrino cooling, and the non-radial motions increase the dwell time of fluid elements in the gain region, thereby increasing the time they are subject to neutrino heating.…”
Section: Development Of Instabilities and Asphericitymentioning
confidence: 82%
“…A number of early multidimensional hydrodynamics simulations demonstrated that neutrino-driven convection does indeed develop in the heating layer and enhances the revival of the shock (Herant et al 1992(Herant et al , 1994Janka & Müller 1993Burrows et al 1995). These authors and others pointed out that convectively unstable entropy gradients occur in the heating layer for several reasons.…”
Section: Development Of Instabilities and Asphericitymentioning
confidence: 99%
See 1 more Smart Citation
“…The shock is distorted by this convective activity. In the Herant et al [4] simulations, large-scale convection developed beneath the shock, leading to increased neutrino energy deposition, the accumulation of mass and energy in the gain region, and a thermodynamic engine they claimed ensured explosion, although Herant et al stressed the need for more sophisticated multidimensional, multigroup transport in future models. [They used two-dimensional "gray" (neutrino-energy-integrated, as opposed to multigroup) flux-limited diffusion in neutrino-thick regions and a neutrino lightbulb approximation in neutrinothin regions.…”
Section: Neutrino-driven Convection (2d)mentioning
confidence: 99%
“…The heating is mediated primarily by the absorption of electron neutrinos and antineutrinos on the dissociation-liberated nucleons behind the shock. This past decade has also seen the emergence of multidimensional supernova models, which have investigated the role convection, rotation, and magnetic fields may play in the explosion [4][5][6][7][8][9][10], in some cases invoking new explosion paradigms.…”
Section: Introductionmentioning
confidence: 99%